2022
DOI: 10.21203/rs.3.rs-1019411/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Serotonin regulation of behaviour via large-scale neuromodulation of serotonin receptor networks

Abstract: Although we understand how serotonin receptors function at the single-cell level, what role different serotonin receptors play in regulating brain-wide activity and, in turn, human behaviour, remains unknown. Here, we developed transcriptomic-neuroimaging mapping to characterise brain-wide functional signatures associated with specific serotonin receptors: serotonin receptor networks (SRNs). Probing SRNs with optogenetics-fMRI and pharmacology in mice, we show that activation of dorsal raphe serotonin neurons … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 76 publications
(118 reference statements)
0
4
0
Order By: Relevance
“…Inhibition of norepinephrine reuptake improves motor learning in healthy adults 44 . Serotonin is also a potent modulator of several cortical neurochemical systems and brain networks 45,46 . However, noradrenergic, serotonergic, and cholinergic dysfunction are more often related to cognitive than motor deficits in PD 22,30,32,41,[47][48][49] .…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of norepinephrine reuptake improves motor learning in healthy adults 44 . Serotonin is also a potent modulator of several cortical neurochemical systems and brain networks 45,46 . However, noradrenergic, serotonergic, and cholinergic dysfunction are more often related to cognitive than motor deficits in PD 22,30,32,41,[47][48][49] .…”
Section: Discussionmentioning
confidence: 99%
“…The resulting molecular-enriched networks can be compared between groups (e.g., patients vs controls), conditions (e.g., rest vs naturalistic stimuli), or states (e.g., drug vs placebo) as well as correlated with variables of interest (eg: clinical, 13 psychometric, or pharmacokinetic measures). This approach integrating molecular information into fMRI networks has been recently extended to gene expression data and used to examine receptor-enriched networks in both mice and humans using gene expression data from the Allen Mouse/Human Brain atlases to derive so-called "serotonin receptor networks (SRNs)" (Salvan et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…One unexplored avenue is the use of blocking studies, within which the effects of a drug on molecular networks can be examined with and without an antagonist to the primary target, providing a causal manipulation of the system of interest which should be reflected in the molecular networks. Another option would be to utilise manipulations of molecular systems within animal models, as recently done by Salvan and colleagues (Salvan et al, 2022) to show that pharmacological and optogenetic manipulation of the serotonergic system modulates the SRNs in a receptor sub-system-specific manner. A similar study has also recently shown that the serotonin receptor gene expression patterns explain a large proportion of the variance in the BOLD signal following optogenetic stimulation of the dorsal raphe (Hamada et al, 2022).…”
Section: Methodical Considerations and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation